2019
DOI: 10.1123/ijspp.2018-0553
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Anaerobic Speed Reserve Testing in the Field: Validation of vVO2max Prediction From 1500-m Race Performance in Elite Middle-Distance Runners

Abstract: Purpose: Anaerobic speed reserve (ASR), defined as the speed range from velocity associated with maximal oxygen uptake (vVO2max) to maximal sprint speed, has recently been shown to be an important tool for middle-distance coaches to meet event surge demands and inform on the complexity of athlete profiles. To enable field application of ASR, the relationship between gun-to-tape 1500-m average speed (1500v) and the vVO2max for the determination of lower landmark of the ASR was assessed in elite middle-distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(70 citation statements)
references
References 12 publications
6
57
1
Order By: Relevance
“…The finding in the present study that ASR was approximately similar between the fastest and the slowest runners was not surprising in light of the results from Sandford et al (2019a,b). When finding that ASR was positively related to 800-m performance and negatively related to 1,500-m performance, Sandford et al (2019b) stressed that ASR in isolation is not indicative of an athlete's caliber. As in the present study, Sandford et al (2019b) showed that with a higher MAS, but not a higher MANS, ASR becomes lower although the higher MAS in itself would contribute to a better performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding in the present study that ASR was approximately similar between the fastest and the slowest runners was not surprising in light of the results from Sandford et al (2019a,b). When finding that ASR was positively related to 800-m performance and negatively related to 1,500-m performance, Sandford et al (2019b) stressed that ASR in isolation is not indicative of an athlete's caliber. As in the present study, Sandford et al (2019b) showed that with a higher MAS, but not a higher MANS, ASR becomes lower although the higher MAS in itself would contribute to a better performance.…”
Section: Discussionmentioning
confidence: 99%
“…When finding that ASR was positively related to 800-m performance and negatively related to 1,500-m performance, Sandford et al (2019b) stressed that ASR in isolation is not indicative of an athlete's caliber. As in the present study, Sandford et al (2019b) showed that with a higher MAS, but not a higher MANS, ASR becomes lower although the higher MAS in itself would contribute to a better performance. The present results that the runners with the highest ASR had the lowest MAS support the findings by Ortiz et al (2018) who demonstrated a positive correlation between MANS and ASR, but a negative correlation between MAS and ASR in soccer players.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While traditional endurance disciplines can be described as maximization challenges (i.e., training that enhances VO 2max or fractional utilization is "always positive" for performance), we propose that the 800-m event in particular requires an energy release optimization strategy that respects the interactions and trade-offs between anaerobic and aerobic metabolism emerging in both training and performance. This complexity allows internationally successful middledistance runners to present a variety of physiological profiles [12][13][14][15]. For example, VO 2max ranges from ~ 65 to 85 ml•kg•min −1 in elite men [16,29,70,71].…”
Section: The Energetic Side Of the Middle-distance Coinmentioning
confidence: 99%
“…Despite an increasing amount of research devoted to middle-distance training [e.g., [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], it is reasonable to argue that the developments in these disciplines have not been driven by sport scientists [18]. Publicly available "recipe books" and training diaries based upon the practical experience and intuition of world-leading athletes and coaches have become important and popular sources of best practice training information and framework development for the international middle-distance community (Table 1).…”
Section: Introductionmentioning
confidence: 99%